Teaching research methods in political science - Bernstein, Jeffrey L.; Edward Elgar Publishing (Northampton : Edward Elgar Publishing, 2021)
"Teaching Research Methods in Political Science brings together experienced instructors to offer a range of perspectives on how to teach courses in political science. It focuses on numerous topics, including identifying good research questions, measuring key concepts, writing literature reviews and developing information literacy skills. Illustrating the ways in which research methods courses connect with wider topics in political science, contributors discuss how methodological considerations can result in recognition of previously silenced voices, and consider the civic education mission of research methods in political science. Chapters outline quantitative and qualitative methods, feminist methodologies and techniques for studying African-American politics, to review and demonstrate the many avenues that instructors of research methods courses might take. This crucial guide to teaching will benefit instructors of courses in research methods in political science, as well as faculty leaders instituting new courses in political science. Its theoretical insights into civic education will also be useful to scholars of education more broadly"--
Introduction: The citizenship imperative and the political science research methods course / Jeffrey L. Bernstein -- Part I. Guidance for teaching the research methods course -- 1. Getting the basics right: Finding the right research question / Zsolt Nyiri -- 2. Incorporating information literacy in political science research design / Amanda Shannon and Vaughn Shannon -- 3. Beyond the annotated bibliography: Improving student literature reviews through structured heuristics / Shane Nordyke and Peter Yacobucci -- 4. Promoting course coherence by teaching with an invisible pet and other case studies / Kristin Makszin -- 5. Effectively teaching research methods as a series of simulation exercises / Jason Enia -- 6. Political methodology without the politics: Reshaping the methods course to focus on real-world content and skill building / Amanda M. Rosen -- 7. Engaged statistics: Building statistical skills by focusing on answering interesting and important questions / Michael A. Bailey -- 8. Teaching transparency: Principles and practical considerations with illustrations in Stata and R / Matthew C. Ingram -- 9. Effectively teaching research methods in an online course / Robert Postic -- Part II. Fitting research methods within the broader curriculum and discipline -- 10. Designing and implementing methods curricula / Johan Adriaensen, Patrick Bijsmans and Afke Groen -- 11. Scaffolding research methods across the curriculum: An exploration of embedded curricular design / Kelly A. Clancy and Kelly Bauer -- 12. Incorporating and assessing methods across the political science curriculum / Christi Siver and Claire Haeg -- 13. Are students failing research methods or are research methods failing students? / William D. Blake and Carolyn Forestiere -- 14. What the traditional critiques from marginalized groups bring to comprehending political science research today / Harwood K. McClerking -- 15. Mainstreaming gender in research methods / Alexis Leanna Henshaw -- 16. A Dewe
Includes bibliographical references and index.
Keywords: elektronické knihy; electronic books; Political science -- Research -- Methodology -- Study and teaching; Civics -- Study and teaching